Optimizing the Management of Educational Facilities and Infrastructure Based on Islamic Values - Rade Nugraha; Adia Rindani; Syafaatul Habib (LP3M KH Yazid Karimullah Institute, 2025)
The management of educational facilities and infrastructure has a vital role in creating quality, effective and efficient education. This research aims to analyze the governance of educational facilities from an Islamic perspective through the literature study method. Data were collected from books, journals and documents related to education management and Islamic principles. The results show that good governance contributes to improving the quality of learning and creating a conducive environment. In the Islamic view, management not only emphasizes material aspects, but also spiritual values such as justice, trust, transparency and responsibility. The application of these principles is important to build an education system that not only educates intellectually, but also shapes the character and morals of students. Thus, optimal management supports the creation of holistic and sustainable education in facing global challenges.